Transformation of Zakat Payroll Based on Sociopreneur In Baznas Gresik Regency Perspective of Maslahah - Najah, Ahmadun; Dikuraisyin, Basar (Syekh Ali Hasan Ahmad Addary State Islamic University, 2025)
This research describes the harmonisation strategy carried out by BAZNAS Gresik Regency against the controversy over the implementation of zakat payrool. Harmonisation is done through zakat impactum, which makes professional zakat muzakki as mustahik empowerment partners through the concept of sociopreneur. In the legal context, zakat payrool is controversial because it contains unilateral imposition of employee salaries for zakat obligations, but, on the other hand, the imposition is in line with maslahah. This research takes a sample of implementation in BAZNAS Gresik Regency and harmonisation strategy, then the strategy is analysed from maslahah perspective to produce a legal pattern that contains goodness. Therefore, this research is qualitative in nature by taking interview data from amil zakat in BAZNAS and some assisted mustahik as primary data. Analysis is needed to test the interview results through triangulation analysis. The research findings show that the implementation of zakat payrool contains maslahah mulghah which is in line with the demands of zakat obligation, even more maslahah than punishment. The harmonisation strategy to prevent problems is done by making muzakki as auditors and partners in using zakat funds for mustahik businesses. This is in accordance with the maqasid of sharia, namely protecting wealth and developing it.